Strategi Komunikasi Melalui Media Visual Penyuluh Agama Hindu Pada Masa Pandemi Covid-19 di Kota Mataram - Ni Nyoman Harnika (Jurnal SASAK : Desain Visual dan Komunikasi, 2020)
The Covid-19 pandemic has a large influence on the social interactions of Hindu religious counselors to communicating Hindus religious teachings. This is due to government policies that apply social distancing or keep a distance of one to two meters, and do not involve large numbers of people who can cause crowds. This policy has led to changes in the social interaction of a Hindu religious counselor in carrying out his duties as an instructor in communicating Hindu"s religious teachings.This study used a qualitative research method that took place in the city of Mataram, with the object of research being Hindu religious extension workers who had a duty area in the city of Mataram.The communication strategy carried out by Hindu religious counselors during the Covid-19 pandemic was to use visual media in the form of pictorial messages containing religious teachings, animations containing stories containing moral messages and religious teachings, and spiritual videos from Hindu saints. This visual media is channeled using whatshap social media because it is considered very effective in disseminating information, is widely used and known to the public. Information is disseminated through group messages, then discussions and questions and answers are held in each group to find out the audience or communicant's feedback. Group communication through whatshap group chat is able to bridge communication between Hindus religious counselors and the assisted community during a pandemic where direct contact and mass gathering in large numbers cannot be carried out.